Cognitive Semantic Analysis of Metaphors in the Lyrics of Sorai by Nadin Amizah - Harahap, Annisah Inriani; Armis, Muhammad Khairi (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2025)
The research aims to analyze the use of metaphor in the lyrics of the song "Sorai" by Nadin Amizah using a descriptive qualitative approach. The data collection method used in this study is the observation technique. Subsequently, the data analysis was conducted using the categorization technique. In the data analysis, the researcher categorized the metaphors in the song based on their types according to Parera's theory. From the conducted data analysis, it was found that in the song "Sorai," the songwriter used various types of metaphors to depict their feelings. There are three types of metaphors based on Parera's theory that are used in the song, namely anthropomorphic metaphors, abstract to concrete metaphors, and anesthesia metaphors. The most frequently used metaphor is the abstract to concrete metaphor, with a total of five instances. The anthropomorphic metaphor has four instances, while the anesthesia metaphor only appears once.